The INFLUENCE OF TIKTOK SOLO TRAVELING @JADIGINIGINIMI SOCIAL MEDIA CONTENT ON MEETING THE NEEDS OF TOURISM INFORMATION IN GENERATION Z - Ratih Hasanah; Ananda Nurul Fauziyah (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2024)
The solo traveling trend continues to grow, especially among the younger generation or generation Z. The development of information and communication technology has changed the way people access and utilize information, including tourist information. Social media, especially TikTok, has become a popular platform among generation Z to find inspiration and information about various tourist destinations. This research aims to identify how much influence TikTok content has solo traveling towards fulfilling the tourism information needs of generation z. The method used is a quantitative method by distributing questionnaires via google form and process screening questions. The analysis techniques used are descriptive analysis, normality test, heteroscedasticity, correlation coefficient test, determination test, and T test. The results of the research show that TikTok @jadiginimi content has a significant influence in meeting the tourism information needs of generation Z. Tests that have been carried out previously have provided results. that variable (x) 'social media content' has an influence of 51.8% on variable (y) fulfilling tourism 'information needs' in generation Z, while the remaining 48.2% is another factor that was not researched. Thus, this research can provide insight into the role of social media in disseminating tourism information and Generation Z's preferences in consuming travel content in the future. Keywords: Content, Information Needs, Social Media, TikTok, Solo Traveling.